Multifractal detrended cross-correlation analysis of Islamic stock markets in the pacific Asia region - Soufiane, Benbachir; Karim, Amzile (Edelweiss Applied Science and Technology, 2025)
This study aims to uncover the multifractal characteristics and complex interactions among six Islamic stock markets in the pacific Asia region, enhancing understanding of their dynamics. Employing Multifractal Detrended Cross-Correlation Analysis (MF-DCCA), this research analyzes a dataset covering the period from January 1, 2011, to August 1, 2024, with approximately 3315 observations. In the preliminary analysis, the application of the DCCA Cross-Correlation Coefficient method revealed that the cross-correlations are persistent and exhibit long-term stability across most index pairs. Utilizing core components of the MF-DCCA method, such as Generalized Hurst Exponents, Rényi Exponents, and the Hölder Singularity Spectrum, further confirmed that the index pairs exhibit long-range persistent cross-correlations and multifractal behavior. Surrogate and shuffling transformations showed that the observed multifractality is influenced by both long-term cross-correlations and heavy-tailed distributions. The findings have important implications for investors, policymakers, and financial analysts concerned with portfolio diversification, risk management, and the efficiency of Islamic financial markets in this economically vital region. Understanding the interconnectedness of these markets can aid in developing more effective investment strategies and regulatory frameworks. This study contributes original insights into the dynamics of Islamic stock markets in the Pacific Asia region, offering a nuanced perspective on their complex behaviors and interactions through the lens of multifractality.